Content of Crude Protein, Crude Fiber, and Crude Fat Kepok Banana Peel Fermented with SOC at Different Times - Risdawati Br. Ginting; Puteri (International Forum of Researchers and Lecturers, 2023)
Banana peel is banana processing waste that can be used as poultry feed, but because of its high crude fiber content, it is necessary to do processing to reduce it, one way is by processing processes such as fermentation. The fermentation process takes time to get good nutritional results. This study aims to determine the content of crude protein, crude fiber and crude fat of banana peels fermented with SOC at different times. This study used an experimental method with a Complete Randomized Design with three treatments and six repeats. The three treatments are W0= (0 hours), W1= 24-hour fermentation, and W2= 72-hour fermentation. The observation parameters are crude protein content, crude fiber, and crude fat. The results showed that the SOC Fermented Kepok banana peel nutrition showed the highest crude protein analysis results were P2 with an average crude protein of 22.14% and differed very markedly from P1 and P0, with the lowest crude protein average at P0: 10.20%. The results of the analysis of the highest crude fiber content were P0 with an average crude fiber of 22.38% and differed very significantly from P1 and P2 with the lowest average crude fiber at P2: 15.30%. The highest crude fat content analysis was P2 with an average crude fat of 16.67% and differed markedly from P1 and P0, with the lowest average crude fat at P0; 13,71%. Fermentation of kapok banana peel with SOC for 72 hours produced 22.14% protein, 15.30 crude fiber, and 16.67% crude fat.